Stakeholder consultation workshop on "Co-Lab: the virtual collaboration platform for Digital Agri-food Systems" in Pune, India - Sajji, Sherin; Nagaraji, Satish (CGIAR, 2023)
The stakeholder Consultation workshop on “Co-Lab: The Virtual Collaboration Platform for Digital Agri-food Systems” was convened in July 2023 as an interactive discussion to brainstorm ideas and get feedback about the collaboration platform. The workshop brought together 14 stakeholders, both in person and remotely, representing agri-tech startups and CGIAR. Participants found that the workshop offered them a platform to codesign the Co-Lab platform for which they enthusiastically engaged in the brainstorming session, scoping potential South-South collaboration opportunities. Based on the participants' feedback, the Digital Innovation Initiative will refine and enhance the Co-Lab platform's features.